1997
DOI: 10.1007/bf01301430
|View full text |Cite
|
Sign up to set email alerts
|

Study of the course of the incidence angle during growth

Abstract: Standing posture is made possible by hip extension and lumbar lordosis. Lumbar lordosis is correlated with pelvic parameters, such as the declivity angle of the upper surface of the sacrum and the incidence angle, which determine the sagittal morphotype. Incidence angle, which is different for each individual, is known to be very important for upright posture, but its course during life has not yet been established. Incidence angle was measured on radiographs of 30 fetuses, 30 children and 30 adults, and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
3
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 10 publications
6
91
3
7
Order By: Relevance
“…As Labelle et al [11,12], we fully recognize that there was a difference in age between our spondolisthesis cohort and our asymptomatic volunteers used for comparison. However, we believe our conclusion, little affected by this difference despite in normal individuals the PI gradually increasing with age from the onset of walking to late childhood [14,15]. Other studies have suggested that this parameter increase with age but remain stable after the age of 10 [17].…”
Section: Discussionmentioning
confidence: 47%
“…As Labelle et al [11,12], we fully recognize that there was a difference in age between our spondolisthesis cohort and our asymptomatic volunteers used for comparison. However, we believe our conclusion, little affected by this difference despite in normal individuals the PI gradually increasing with age from the onset of walking to late childhood [14,15]. Other studies have suggested that this parameter increase with age but remain stable after the age of 10 [17].…”
Section: Discussionmentioning
confidence: 47%
“…It stays then steady during the adult period. In the same way, the adaptation and the progressive establishment of the sagittal spinal curvatures occur during the childhood [15,16].…”
Section: Discussionmentioning
confidence: 86%
“…In the current study, we present a comparison of the sagittal spinopelvic alignment between 2 groups of SD individuals, namely those that are skeletally immature (Risser's sign of 0, 1, 2, or 3) to those who are skeletally mature (Risser's sign of 5). Since PI has been reported to increase during childhood and adolescence and to remain constant when skeletal maturity is reached [6,9,10], we find it important to consider the skeletal maturity in such analyses. All of the patients with Risser's sign of 4 were excluded from the current study, because of data inconsistency: although Risser's sign of 4 has been thought as an indicator of vertebral growth cessation, there are reports emphasizing that at this stage of maturation some residual growth activity remains, and thus a potential for changes in pelvic morphology exists [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic incidence is hypothesized to be the fundamental pelvic parameter for three-dimensional regulation of spinal sagittal curves [8]. It is accepted that PI becomes fixed with skeletal maturation and remains constant in adulthood, unless there is a pathological process that can modify the shape of the pelvis [6,9,10]. Deviations in pelvic morphology and subsequently higher values of PI were found to be associated with spondylolisthesis and idiopathic scoliosis [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%